2019
DOI: 10.5578/turkjsurg.4117
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and laboratory markers used to predict leakage in esophagojejunal anastomotic leakage after total gastrectomy

Abstract: Objective: Esophagojejunal anastomotic leakages, which occur in the reconstruction procedures performed after total or proximal gastrectomy, still account for one of the most significant causes of morbidity and mortality in spite of the developments seen in perioperative management and surgical techniques in gastric cancer surgery. The aim of the present study was to ascertain the risk factors for Esophagojejunal anastomotic leakages. Material and Methods: A total of 80 patients with gastric cancer, who had to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
3
6
0
1
Order By: Relevance
“…One the other hand, the decrease in hemoglobin resulting from extensive blood loss will weaken the oxygen-carrying capacity, thereby causing anastomotic leakage. Three previous studies [1,6,10] reported that longer duration of operation and combined organ resection including splenectomy or pancreatectomy were associated with anastomotic leakage, increasing the risk of morbidity. However, the present study failed to reach this conclusion, and the main reason for this may lie in staff experience and the use of optimized mechanical devices, which make the surgery faster and more secure, ultimately decreasing the incidence of anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One the other hand, the decrease in hemoglobin resulting from extensive blood loss will weaken the oxygen-carrying capacity, thereby causing anastomotic leakage. Three previous studies [1,6,10] reported that longer duration of operation and combined organ resection including splenectomy or pancreatectomy were associated with anastomotic leakage, increasing the risk of morbidity. However, the present study failed to reach this conclusion, and the main reason for this may lie in staff experience and the use of optimized mechanical devices, which make the surgery faster and more secure, ultimately decreasing the incidence of anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EJAL has been identi ed as an independent negative prognostic factor for long-term survival [1]. The reported incidence of EJAL varies between 0.5% and 11.5% [1][2][3][4][5][6][7][8][9], and recently, Cetin DA [10] even reported an incidence of up to 16.2%. These data highlight the requirement for the prevention of complications at the perioperative stage.…”
Section: Introductionmentioning
confidence: 99%
“…Одним из главных условий безопасного применения ПУВ является раннее выявление возможных осложнений и принятие соответствующих мер. Наиболее грозным осложнением в хирургии РЖ является несостоятельность ЭЕА, частота которой, по данным разных авторов, составляет от 1,1 до 16,2 % [47][48][49][50]. В структуре локальных инфекционных осложнений после ГЭ инфильтраты и абсцессы составляют от 1,4 до 5,5 % [5,49].…”
Section: с-реактивный белок в диагностике осложненийunclassified
“…The common biomarkers that predict the occurrence of surgical complications include C-reactive protein (CRP), lactate, leukocytes, percentage of neutrophils, and procalcitonin [4–9] . However, there are only a few studies on the use of biomarkers to predict the complications after esophagectomy, even most of these studies are merely about anastomotic leakage [6–10] …”
Section: Introductionmentioning
confidence: 99%